Impact of the Latitude of Stratospheric Aerosol Injection on the Southern Annular Mode. Issue 19 (29th September 2022) - Bednarz, Ewa M.; Visioni, Daniele; Richter, Jadwiga H.; Butler, Amy H.; MacMartin, Douglas G.
Abstract: The impacts of Stratospheric Aerosol Injection (SAI) strategies on the Southern Annular Mode (SAM) are analyzed with the Community Earth System Model. Using a set of simulations with fixed single‐point SO2 injections we demonstrate the first‐order dependence of the SAM response on the latitude of injection, with the northern hemispheric and equatorial injections driving a response corresponding to a positive phase of SAM and the southern hemispheric injections driving a negative phase of SAM. We further demonstrate that the results can to first order explain the differences in the SAM responses diagnosed from the two recent large ensembles of geoengineering simulations utilizing more complex injection strategies – Geoengineering Large Ensemble and Assessing Responses and Impacts of Solar climate intervention on the Earth system with Stratospheric Aerosol Injection (GLENS and ARISE‐SAI) – as driven by the differences in the simulated sulfate aerosol distributions. Our results point to the meridional extent of aerosol‐induced lower stratospheric heating as an important driver of the sensitivity of the SAM response to the injection location. Plain Language Summary: Stratospheric Aerosol Injection (SAI) is a proposed climate intervention method in which sulfate aerosol precursors are injected into the lower stratosphere to mitigate some of the negative impacts of climate change. Here we analyze SAI impact on the Southern Annular Mode (SAM), a dominant mode of interannual climate variability in the southern mid‐ and high latitudes, using the Community Earth System Model. Using a set of simulations with fixed single‐point injections of aerosol precursors we demonstrate the first‐order dependence of the SAM response on the latitude of injection, with the northern hemispheric and equatorial injections driving a response corresponding to a positive phase of SAM and the southern hemispheric injections driving a negative phase of SAM. We further demonstrate that our results can to first order explain the differences in the SAM responses diagnosed from the two recent large ensembles of geoengineering simulations utilizing more complex injection strategies as driven by the differences in the simulated sulfate aerosol distributions. Our findings illustrate the complex interplay of the microphysical, radiative and dynamical processes contributing to the SAI responses on regional scales. Key Points: Stratospheric Aerosol Injection (SAI) impacts the Southern Annular Mode (SAM), and the response is strongly sensitive to the latitude of SAI Injections in the Northern Hemisphere drive positive SAM response and injections in the Southern Hemisphere drive negative SAM response Meridional extent of lower stratospheric aerosol heating likely an important contributor to the sensitivity to injection latitude